MicroRNA-Mediated Direct Reprogramming of Human Adult Fibroblasts Toward Cardiac Phenotype - Paoletti, C.; Divieto, C.; Tarricone, G.; Di Meglio, F.; Nurzynska, D.; Chiono, V. (Frontiers in Bioengineering and Biotechnology, 2020)
Modulation of microRNA expression holds the promise to achieve direct reprogramming of fibroblasts into cardiomyocyte-like cells as a new strategy for myocardial regeneration after ischemic heart disease. Previous reports have shown that murine fibroblasts can be directly reprogrammed into induced cardiomyocytes (iCMs) by transient transfection with four microRNA mimics (miR-1, 133, 208 and 499, termed “miRcombo”). Hence, study on the effect of miRcombo transfection on adult human cardiac fibroblasts (AHCFs) deserves attention in the perspective of a future clinical translation of the approach. In this brief report, we studied for the first time whether miRcombo transient transfection of AHCFs by non-viral vectors might trigger direct reprogramming of AHCFs into cardiomyocyte-like cells. Initially, efficient miRNA delivery to cells was demonstrated through the use of a commercially available transfection agent (DharmaFECT1). Transient transfection of AHCFs with miRcombo was found to upregulate early cardiac transcription factors after 7 days post-transfection and cardiomyocyte specific marker cTnT after 15 days post-transfection, and to downregulate the expression of fibroblast markers at 15 days post-transfection. The percentage of cTnT-positive cells after 15 days from miRcombo transfection was ~11%, as evaluated by flow cytometry. Furthermore, a relevant percentage of miRcombo-transfected AHCFs (~38%) displayed spontaneous calcium transients at 30 days post-transfection. Results evidenced the role of miRcombo transfection on triggering the transdifferentiation of AHCFs into iCMs. Although further investigations are needed for iCM maturation, early findings from this study pave the way towards new advanced therapies for human cardiac regeneration.